High performance system for the interactive rendering of a 3D model into MPEG-4 - Joshi, A.; Ismail, S.; Taqa, A.; Ng, L.S. (2011)
The goal of the project is to create a Multiprocessor system capable of rendering a 3D model into an MPEG-4 stream. This paper outlines the design, software architecture and hardware setup for the system. Preliminary success in the previous setup1 helped us gain experience as well as motivation for this highly optimized and powerful second version.